Gravity Wave Breaking Associated with Mesospheric Inversion Layers as Measured by the Ship-Borne BEM Monge Lidar and ICON-MIGHTI - Robin Wing (MDPI AG, 2021)
During a recent 2020 campaign, the Rayleigh lidar aboard the Bâtiment d’Essais et de Mesures (BEM) Monge conducted high-resolution temperature measurements of the upper Mesosphere and Lower Thermosphere (MLT). These measurements were used to conduct the first validation of ICON-MIGHTI temperatures by Rayleigh lidar. A double Mesospheric Inversion Layer (MIL) as well as shorter-period gravity waves was observed. Zonal and meridional wind speeds were obtained from locally launched radiosondes and the newly launched ICON satellite as well as from the European Centre for Medium-Range Weather Forecasts (ECMWF-ERA5) reanalysis. These three datasets allowed us to see the evolution of the winds in response to the forcing from the MIL and gravity waves. The wavelet analysis of a case study suggests that the wave energy was dissipated in small, intense, transient instabilities about a given wavenumber in addition to via a broad spectrum of breaking waves. This article will also detail the recent hardware advances of the Monge lidar that have allowed for the measurement of MILs and gravity waves at a resolution of 5 min with an effective vertical resolution of 926 m.